Предмет: Математика,
автор: sasha21312441
(4+5x)-3(2-x)=16x-0,4
2x+0,1-4(1-4x)=8x-4,4
Ответы
Автор ответа:
0
(4+5x)-3(2-x)=16x-0,4
4+5х-6+3х=16х-0,4
5х+3х-16х=-0,4-4+6
-8х=1,6
х=1,6:(-8)
х=-0,2
2x+0,1-4(1-4x)=8x-4,4
2х+0,1-4+16х=8х-4,4
2х+16х-8х=-4,4-0,1+4
10х=-0,5
х=-0,5:10
х=-0,05
4+5х-6+3х=16х-0,4
5х+3х-16х=-0,4-4+6
-8х=1,6
х=1,6:(-8)
х=-0,2
2x+0,1-4(1-4x)=8x-4,4
2х+0,1-4+16х=8х-4,4
2х+16х-8х=-4,4-0,1+4
10х=-0,5
х=-0,5:10
х=-0,05
Похожие вопросы
Предмет: Биология,
автор: litvakzena0061
Предмет: Физика,
автор: lelaevau
Предмет: Физика,
автор: zalgasbajzhiger53
Предмет: Математика,
автор: саид2005